Influence of heavy Hf doping in CeO2: Prediction on various physical properties - Khandaker Monower Hossain; Sujon Kumar Mitro; Samina Afrin Moon; M. Mozahar Ali; Sumal Chandra; M. Anwar Hossain (Results in Physics, 2022)
This work employs density functional theory for calculating the structural, mechanical, anisotropic, thermal, electronic, and optical properties of Ce1-xHfxO2 (x = 0, 0.25, 0.5, and 0.75) to explore the heavy substitutional doping effects of Hf. The cubic phase of CeO2 is transformed to tetragonal when 50% Ce is replaced by Hf. The computed formation energy and elastic constants demonstrate the phase stability of studied materials. The present calculation demonstrates the ductility of both undoped and Hf-doped CeO2, but the tetragonal Ce0.5Hf0.5O2 reveals highest ductility as compared to other phases. Moreover, the tetragonal phase is the most anisotropic one than that of other phases. Interestingly, both pure and doped phases are acceptable for thermal barrier coating, however doping with 75% Hf at Ce-site makes it even more suitable. The semiconducting nature of CeO2 is evolved because of having band gap in the electronic band structure, which is supported by its experimental report. The band gap is increased with increasing doping of Hf. The optical absorption and conductivity reconfirm the semiconducting nature of the titled materials. Furthermore, the overall optical nature predicts the efficient uses of Ce1-xHfxO2 in microelectronics, integrated circuits, and solar panel.